Determination Of Beclomethasone Dipropionate, Clotrimazole, Chloramphenicol And Lidocaine In Pharmaceutical Formulations Using A Novel Rp-Hplc Method - Useni Reddy Mallu; K. Hussain Reddy; Varaprasad Bobbarala; Somasekhar Penumajji (International Journal of Pharma and Bio Sciences, 2011)
The aim of this study was to develop a RP-HPLC method for determining the contents of beclomethasone dipropionate, clotrimazole, chloramphenicol and lidocaine in ear drops formulation. Chromatographic separation was achieved on a Octa-decyl silane (C18) column with a simple gradient program, mobile phase is Sol-A: buffer(1.6g of CH3COONH2 in to 1000mL of HPLC grade water, add 10mL of TEA and adjust the pH to 6.4± 0.1 with diluted acetic acid) and Sol-B: Acetonitrile. 1.0ml per min flow rate and detection was at 254 nm. Chloramphenicol, lidocaine, belclomethasone dipropionate and clotrimazole were eluted at 5.0min, 10.8min, 16.2min and 19.1min, respectively. The absorbance of four active peaks was a linear function of concentration in the range 1.0ppm to 6.0ppm for Beclomethasone Dipropionate, 187.5ppm to 1125.0ppm for Chloramphenicol, 37.5ppm to 225.0ppm for Clotrimazole and 65ppm to 390ppm for Lidocaine, correlation coefficients of Beclomethasone Dipropionate is 0.9997, Chloramphenicol is 0.9999, Clotrimazole is 0.9998 and Lidocaine is 0.9999 respectively. The reverse-phase HPLC assay method was developed and validated. The method has wide applicability for these four active ingredients. The method has reproducibility, accuracy and robust.